Aplicación móvil para diseñadores con la finalidad de crear fuentes de trabajo y cubrir las necesidades del cliente en el cantón Latacunga. - Palomo Quinatoa, Pablo Javier (2020)
The purpose of this research project is to design a prototype of a mobile application that allows to capture professional work and incorporate the location network of graphic designers and design printing centers in Latacunga’s city, in order to achieve a fast location, eradicating the bonds of friendship and family, providing opportunities for graphic designers to demonstrate their respective capabilities and performance in their work area, The idea is aimed at the structural design of a mobile application prototype, which allows the user to learn about the work fields of graphic design, providing a space for information, participation and knowledge. The design of the mobile prototype considers aspects of usability, being attractive to users in the same way also generating a web prototype design, allowing navigation on both mobile and computer. To support the research methodology of the project, bibliographic, documentary, field and projective research was applied, in the same way we used research techniques such as the interview and the survey. The design of the mobile prototype was developed through the methodology of user experience that consists in following a process from research, organization, prototyping, testing, design and due to the web prototype the methodology of the user-centered web design was used. To complete the mobile prototype, it presents ease of use and portability, providing an advantage for graphic design professionals and common users, that is, people who do not have knowledge in the subject but who require of a designer service